DigComp: Methodological frame for measuring digital competencies - Ivanović Đina; Simović Vladimir (Trendovi u Poslovanju)
This review paper is based on a desk study of the Digital Competence Framework - DigComp developed by the European Commission. The framework was based on the results of a survey of a sample of the European Union population, which showed that a large percentage had underdeveloped digital skills. The aim of this paper is to review the current state of the literature, which is based on the existing DigComp framework, its fields and skills within those areas, which covers the territory of the Republic of Serbia in addition to the other countries. Besides that, a comparison was made of certain areas of the DigComp 2.0 framework with previous ones (DigComp 1.0), and a brief overview of their implementation in practice. It was found that there was space for further study of this topic, and this contributed to the identification of directions for future research. The next step will be to measure students' digital skills.